2001
DOI: 10.1111/j.1099-1123.2001.00329.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Factors Affecting Internal Audit Independence and Objectivity: Evidence from Singapore

Abstract: This study examines two factors that may in uence the independence and objectivity of internal audit. The rst, affecting the organizational independence of the internal audit function, is its relationship with the audit committee. The second is the use of the function as a management training ground. It is argued that this practice might affect individual objectivity because internal auditors may be reluctant to withstand pressure from an auditee who could be their future supervisor. A survey of chief internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
170
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(180 citation statements)
references
References 2 publications
7
170
0
3
Order By: Relevance
“…A comparison with [22] study indicated that 47 percent of the respondents indicate that on average internal auditors in Australia stay for 2 and 4 years in the IAF. A similar study of [12] indicated that 37 percent (20 respondents) indicated that in IAF such a movement to other units was unlikely for internal auditors in Singapore.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…A comparison with [22] study indicated that 47 percent of the respondents indicate that on average internal auditors in Australia stay for 2 and 4 years in the IAF. A similar study of [12] indicated that 37 percent (20 respondents) indicated that in IAF such a movement to other units was unlikely for internal auditors in Singapore.…”
Section: Resultsmentioning
confidence: 95%
“…A comparison with Canadian study of [23] reported that 48 percent of the respondents indicated that AC are involved in the dismissal of the IAF. [12] reported 72 percent in Singapore, [20] reported 50 percent of AC are involved in the appointment evaluation and dismissal of internal audit head in Australia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Auditor mengalami kendala-kendala dalam prakteknya yang membuat ia dilema saat harus membuat keputusan etis (Larkin, 2000;Goodwin dan Yeo, 2001;Thompson, 2003). Auditor internal sering mengalami dilema etis yang menyangkut split loyalty, kesenjangan ekspektasi dan konflik kepentingan antara berbagai pihak (Woodbine dan Liu, 2010).…”
Section: Pendahuluanunclassified
“…This puts internal auditors in a complex situation as their independency can be compromised. The internal audit unit would continue to be independent and effective as long as management allows it to be [13]. It is on the basis of this the researchers sought to undertake this study to assess the support the internal audit units receive from management and how this affects the quality delivery of internal audit services in the public sector.…”
Section: Introductionmentioning
confidence: 99%